Advective hydrogel membrane chromatography for monoclonal antibody purification in bioprocessing. (14th June 2015) - Hou, Ying; Brower, Mark; Pollard, David; Kanani, Dharmesh; Jacquemart, Renaud; Kachuik, Bradley; Stout, James
<x xml:space="preserve">Abstract</x> Protein A chromatography is widely employed for the capture and purification of monoclonal antibodies (mAbs). Because of the high cost of protein A resins, there is a significant economic driving force to seek new downstream processing strategies. Membrane chromatography has emerged as a promising alternative to conventional resin based column chromatography. However, to date, the application has been limited to mostly ion exchange flow through (FT) mode. Recently, significant advances in Natrix hydrogel membrane has resulted in increased dynamic binding capacities for proteins, which makes membrane chromatography much more attractive for bind/elute operations. The dominantly advective mass transport property of the hydrogel membrane has also enabled Natrix membrane to be run at faster volumetric flow rates with high dynamic binding capacities. In this work, the potential of using Natrix weak cation exchange membrane as a mAb capture step is assessed. A series of cycle studies was also performed in the pilot scale device (> 30 cycles) with good reproducibility in terms of yield and product purities, suggesting potential for improved manufacturing flexibility and productivity. In addition, anion exchange (AEX) hydrogel membranes were also evaluated with multiple mAb programs in FT mode. Significantly higher binding capacity for impurities (support mAb loads up to 10Kg/L) and 40X faster processing speed were observed compared with traditional AEX column chromatography. A proposed protein A free mAb purification process platform could meet the demand of a downstream purification process with high purity, yield, and throughput. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:974–982, 2015